MEREDUKSI CACAT BOTOL PLASTIK DENGAN PENDEKATAN SIX SIGMA DAN FUZZY - Nurrakhman, Fahmi Indra; Izzhati, Dwi Nurul (Applied Industrial Engineering Journal, 2019)
Abstract CV Jordan is plastics manufacturing company located in Semarang, Central Java. One of the products produced is PET plastic bottle. In an effort to control products quality, the company has a defects target with maximum value of 2 % per month. However, in fact, the number of product defect increased to 4.69% in October 2018 to March 2019. In this paper, Six Sigma method is used as an approach to overcome the problem of reducing products defects. The stages of Six Sigma method consist of Define, Measure, Analyze, Improve and Control. Even though, the limitation in this paper does not to examine control stage. At Define stage, types of defects identified in PET bottle are leakage, lumpy body, drop test, cut line, shake, convex head, dirty oil, tilted neck, dent ring, slip, pseudo burn, pseudo white, oblique stretch, and thin thickness. Also identified, the cause of dominant defect is the temperature changes in preform machine. The Measure stage, DPMO during the period October 2018 to March 2019 was 46,912 pcs with sigma value of 3.18. Analysis of factors causing defects in the three highest types off defects ie dent ring, pseudo white and rocking are explained at the Analyze stage. In the Improve stage, the temperature of the preform heating machine is stabilized using the fuzzy logic method at 58º Celsius. Keywords : PET, Six Sigma, Quality Control, DMAIC, Fuzzy Abstrak CV Jordan Plastik adalah perusahan plastik yang berada di Semarang. Produk yang dihasilkan diantaranya adalah botol plastik PET. Perusahaan menargetkan maksimal produk cacat rata-rata 2% perbulan, namun realisasinya ada kenaikan produk cacat pada periode Oktober 2018 sampai Maret 2019 menjadi 4,69%. Untuk mengendalikan permasalahan ini dan mereduksi produk cacat, peneliti menggunakan pendekatan Metode Six Sigma.Tahapan dari metode Six Sigma meliputi Define, Measure, Analyze, Improve dan Control. Pada penelitian ini tidak membahas pada tahapan control hanya sampai tahap Improve. Pada tahap Define diketahui jenis cacatnya botol PET yaitu bocor, body menggumpal, drop test, garis motong, goyang, kepala cembung, kotor oli, leher miring, ring penyok, selip, semu gosong, semu putih, stretch miring, dan tebal tipis dan penyebab cacat dominan adalah suhu mesin preform berubah-ubah.Tahap Measure, DPMO selama periode Oktober 2018 sampai Maret 2019 sebesar 46.912 pcs dengan nilai sigma 3,18. Tahap Analyze, analisis faktor yang menyebabkan cacat pada tiga jenis cacat tertinggi yaitu ring penyok, semu putih dan goyang. Pada tahap Improve dilakukan penstabilan suhu mesin pemanas preform dengan metode logika fuzzy pada suhu 58 Celcius. Kata Kunci : PET, Six Sigma, Pengendalian Kualitas, DMAIC, Fuzzy